Belarus : Recent Economic Developments. (IMF Staff Country Reports; Country Report ;, 1995)
This paper describes economic developments in Belarus during 1992-94. The difficult economic situation facing Belarus in 1992 and 1993 continued unabated in 1994. Two political developments compounded the economic problems in the first half of the year. Efforts were aimed at alleviating or mitigating the effects of the downturn in output on living standards in the run-up to the country's first presidential elections. In September 1994, the government developed a comprehensive macroeconomic and structural adjustment program, or 'Anti-Crisis Program,' which was approved by the parliament in October.